The association between health literacy levels and patient-reported outcomes in Japanese type 2 diabetic patients - Haruka Ueno (SAGE Open Medicine, 2019)
Objectives: The aim of this study is to empirically examine a full pathway model of health literacy, and health and well-being outcomes among patients with type 2 diabetes. Methods: A three-wave longitudinal survey was administered to 148 patients with diabetes. Covariance structure analysis was conducted to create a path diagram, with health literacy and burden of medical expenses included as independent variables and with psychosocial factors, behaviors, and health and well-being outcomes included as dependent variables. Results: The model fit indices showed a comparative fit index of 0.985 at baseline, 0.959 after 3 months, and 0.948 after 6 months, with a root mean square error of approximation of 0.040 at baseline, 0.079 after 3 months, and 0.085 after 6 months. There were 14 significant paths across the three time points between health literacy and understanding of diabetes care, self-efficacy, communication with doctors, and medication adherence. Conclusion: The model fitness index showed an adequate result. Health literacy was significantly positively associated with understanding of diabetes care, self-efficacy, communication with doctors, and medication adherence. Health literacy had a direct positive influence on medication adherence and possibly an indirect positive influence on exercise/diet via self-efficacy. The results were generally consistent across the three time points, suggesting good reliability of the models. Improving health literacy may lead to better self-management of diabetes and favorable health outcomes.